Ovid's Erysichthon (Metamorphoses 8.738-878) - Elford, Klarholm C. (My University, 2005)
This thesis examines Ovid's treatment of the Erysichthon narrative at Metamorphoses 8.738-878. It is a specific narratological commentary which, in particular, examines the intertextual relationship between Ovid's Erysichthon narrative and that of Callimachus in his Hymn to Demeter. Chapter One provides a general overview of the passage by reviewing other accounts of the myth, considering the placement of the narrative within Book Eight of the Metamorphoses, and finally, by exploring the role of the narrator and the structure of the narrative. Chapters Two, Three and Four provide detailed literary criticism of Ovid's work. These chapters comprise a specific narratological commentary on Erysichthon's crime, the reaction of others to his behavior, and his punishment.
Keywords: Classics; Classics